PENGARUH MEDIA FILM ANIMASI TERHADAP KEMAMPUAN MENULIS NARASI: STUDI EKSPERIMEN PADA SISWA KELAS V SD NEGERI 13 BIRU KECAMATAN TANETE RIATTANG KABUPATEN BONE - Nurul Pratiwi; H. Sudirman; Sitti Jauhar (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2022)
This research is a quantitative research by quasi research design quasi-experimental that aims to determine whether or not there is a significant effect of using animated film media on the ability to write narratives of fifth grade students of SD Negeri 13 Biru. The variables in this study were animated film media and the students' narrative writing skills. The research population is all fifth grade students of SD Negeri 13 Biru totaling 76 students. Saturated samples have been used, namely class VA for the experimental class and VB for the control class. The research data were obtained by giving a narrative writing test. Data collection techniques used are tests and documentation. The data analysis technique is inferential analysis using the Independent Sample T-test. The results obtained in this research is: (1) There are differences in students' narrative writing abilities between the experimental class and control class where the results of the experimental class students' narrative writing abilities are higher than the control class, (2) There was an effect of the significant use of animated film media on the ability to write narratives.